How much do bank shocks affect investment? Evidence from matched bank-firm loan data - Mary Amiti; David E. Weinstein (Federal Reserve Bank of New York, 2013)
We show that supply-side financial shocks have a large impact on the investment decisions of firms. We do this by developing a new methodology to separate firms' credit shocks from loan supply shocks, using a vast sample of matched bank-firm lending data. We decompose loan movements in Japan for the period 1990 to 2010 into bank, firm, industry, and common shocks. The high degree of financial institution concentration means that individual banks are large relative to the size of the economy, which creates a role for granular shocks, as in Gabaix (2011). As a result, idiosyncratic bank shocks - movements in bank loan supply net of borrower characteristics and general credit conditions - can have large impacts on aggregate loan supply and investment. We show that these idiosyncratic bank shocks explain 40 percent of aggregate loan and investment fluctuations.
Keywords: E44; G21; 330; credit constraints; investment; Kreditgeschäft; Schock; Bank; Kredit; Nachfrage; Investition; Japan